Dual Steganography in Digital Images with Spread Spectrum Insertion Method - Sofia Saidah (JMECS (Journal of Measurements, Electronics, Communications, and Systems), 2019)
This study aims to prove whether embedding a stego-image within another cover can be performed to deceive hackers or unauthorized people. In steganography, both concealing the fact that secret message is sent and its content are concerned. Dual steganography means to make unauthorized people think that the first cover is the real message. The first step is to embed the secret text message into the first cover image using Spread Spectrum (SS) method. After that, the resulting stego-image was transformed using the Discrete Wavelet Transform (DWT) method followed by the insertion process using the Singular Value Decomposition (SVD) method. The result of this study shows that the system can perform dual steganography with good imperceptibility. Parameters measured in the average of 35 dB of PSNR and 30 dB of SNR in the first embedding process; meanwhile, for the second process the system performed in the average of 41 dB of PSNR and 38 dB of SNR. Also, in the extraction process, BER measured close to 0. Although some basic attack scenarios such as Gaussian noise, Salt and Pepper noise, Low Pass Filter (LPF) and High Pass Filter (HPF) were performed in this research, more advanced attack scenarios can be discussed in future research; for instance, compression and geometric transform.